Thermal sensation and comfort in hot and humid climate of Indonesia - Uno, Tomoko; Oka, Daisuke; Hokoi, Shuichi; Ekasiwi, Sri Nastiti Nugrahani; Abdul Majid, Noor Hanita (Springer Singapore, 2018)
In conventional air-conditioning design, the comfortable range is considered to be between temperatures of 25 and 27 ° C and relative humidity of 40 and 60%; these numbers vary only slightly based on a person's race and country. However, several studies conducted in regions with hot and humid climates show that the observed thermal comfort requirements often do not agree with those obtained from European-based studies. In this chapter, the results from the questionnaire surveys and measurements in residences in the hot and humid regions of Indonesia and Malaysia are shown. It was found that the residents use air conditioning at low temperatures for sleeping and that many people consider cold condition as "comfortable" and desire "cooler" conditions even if they feel "cold" in thermal sensation.